The Ability of Second Grade Senior High School Students in Speaking Transactional and Interpersonal Conversation at SMA Negeri 7 Padang - Mona Afersa; Desi Andriani; Pinta Medina; Asma Alhusna (Fakultas Sastra Universitas Ekasakti, 2023)
Speaking is often tested to the students beside listening, reading and writing. Moreover, speaking is an important skill. Students can express their feeling, ideas or opinion through speaking. In addition, students should be able to retell meaning of the monologue and functional texts or produce a transactional/interpersonal dialogue. The object of the data is the second grade students of SMAN 7 Padang. Speaking test was used to get information about the students’ ability in transactional and interpersonal conversation. The indicators are grammar, vocabulary, comprehension, and fluency. Based on the findings and discussion above there are four conclusions that can be drawn in this research. First, the ability of the students in speaking transactional and interpersonal conversation viewed from grammar aspect is fair. Second, the ability of the students in speaking transactional and interpersonal conversation viewed from vocabulary aspect is fair. Third, the ability of the students in speaking transactional and interpersonal conversation viewed from comprehension aspect was fair. Forth, the ability of the students in speaking transactional and interpersonal conversation viewed from fluency aspect is fair.